Limb‐kinetic apraxia affects activities of daily living in Parkinson's disease: a multi‐center study. (1st May 2016) - Foki, T.; Vanbellingen, T.; Lungu, C.; Pirker, W.; Bohlhalter, S.; Nyffeler, T.; Kraemmer, J.; Haubenberger, D.; Fischmeister, F. Ph. S.; Auff, E.; Hallett, M.; Beisteiner, R.
Abstract : Background and purpose: Impaired dexterity (fine hand movements) is often present in Parkinson's disease (PD), even at early to moderate disease stages. It has a detrimental impact on activities of daily living (ADL) such as buttoning, contributing to reduced quality of life. Limb‐kinetic apraxia, a loss of the ability to make precise, independent but coordinated finger and hand movements, may contribute to impaired dexterity even more than bradykinesia per se . However, the impact of limb‐kinetic apraxia on ADL remains controversial. Our aim was to identify the strongest predictor of buttoning and unbuttoning in PD. It was hypothesized that coin rotation (a surrogate of limb‐kinetic apraxia) represents the most important determinant. Methods: Sixty‐four right‐handed, early to moderate PD patients were recruited from three movement disorder centers (Hoehn andYahr stages 1–3). Buttoning, unbuttoning and coin rotation (right and left hand) represented the target tasks. Motor impairment was assessed according to the Unified Parkinson's Disease Rating Scale. Results: Multiple linear regression analysis showed that coin rotation with the right hand was the only significant predictor of buttoning ( P < 0.001) and unbuttoning ( P = 0.002). Notably, measures of bradykinesia or overall motor impairment did not represent significant predictors. Conclusions: Constituting the novel key finding, limb‐kinetic apraxia seems to be particularly relevant for ADL requiring dexterity skills in PD, even at early to moderate disease stages. Our results prompt research into the pathophysiological background and therapeutic options to treat limb‐kinetic apraxia. The simple coin rotation test provides valuable information about ADL‐related dexterity skills.